Controlled formation of metallic tellurium nanocrystals in tellurite glasses using femtosecond direct laser writing - Capelo, Renato Grigolon (2021)
Tellurite glasses are considered a potential alternative for applications not achieved by SiO2-based glasses, presenting interesting optical properties, such as high linear and nonlinear refractive indexes, extended optical window, being also suitable for metallic nanoparticle growth, like Te-0. When doped with sulfide species, it can benefit the reduction of Te4+ to Te-0, which can be advantageous to synthesize in-situ chalcogenide nanoparticles and quantum dots. This work presents investigations on the reduction of Te4+ to Te-0 in tellurite glasses doped with PbS and PbO/ZnS, and aims to control this redox process through the processing with pulsed fs-laser. Tellurite glass samples were synthesized by melt-quenching technique and the thermal and structural properties were explored by different techniques, such as DSC, Raman scattering spectroscopy and mapping experiment, TEM and SAED. Reduction of tellurium to Te-0 nanocrystals into tellurite glass after laser irradiation was studied in detail and confirmed by the presence of bands at similar to 120 and 140 cm(-1) in Raman spectroscopy and mapping, assigned to the Te-Te vibrational modes, which suggest that S2- induces in-situ Te4+ reduction. Moreover, quasi spherical tellurium nanoparticles were observed through TEM and confirmed their chemical nature and crystallization by SAED. The study of tellurium reduction in the vitreous matrix becomes particularly important and promising for some applications, since its reduction generates changes in the refractive index by precipitation of Te-0 nanoparticles, allowing the fabrication of waveguides and as photosensitive material for tridimensional data storage. (C) 2021 Published by Elsevier B.V.